Réponses

2013-12-13T21:16:59+01:00
Bonsoir
A =  V18 +2V8 +4V32 = V(9*2) +2 V(4*2) + 4V(16*2) = 3V2 + 4V2 + 16V2 = 23V2
B = V160 + V40 + V90 = V(16*10) + V( 4*10) + V(9*10) = 4V10 + 2V10 + 3V10 = 12V10

C = (3V5 + V3)²  = (3V5)² + (V3)² + 6V(5*3) = (9*5)+(3) +(6V15) = 48 + 6V15

D = (4V6 - 5V5)² = (4V6)² +(5V5)² - 40V(6*5) = 96 + 125 -40V30 = 221 - 40V30

E = (2-5V7)(2+5V7) = (2)² - (5V7)² = 4 - (25 * 7) = 171 

F = (36V28) / 8V63 = (36V(4*7) ) / (8V(9*7)   simplification par V7 
F = (36*2) / (3*8) = (3*24) / 24 = 3 
il me semble
E = (2-5V7)(2+5V7) = (2)² - (5V7)² = 4 - (25 * 7) = - 171